Trained Immunity in Anopheles gambiae: Antibacterial Immunity Is Enhanced by Priming via Sugar Meal Supplemented With a Single Gut Symbiotic Bacterial Strain - Kulkarni, Aditi; Pandey, Ashmita; Trainor, Patrick; Carlisle, Samantha; Chhilar, Jainder S.; Yu, Wanqin; Moon, Alex; Xu, Jiannong (Frontiers in Microbiology, 2021)
Mosquitoes have evolved an effective innate immune system. The mosquito gut accommodates various microbes, which play a crucial role in shaping the mosquito immune system during evolution. The resident bacteria in the gut microbiota play an essential role in priming basal immunity. In this study, we show that anti-bacterial immunity in Anopheles gambiae can be enhanced by priming via a sugar meal supplemented with bacteria. Serratia fonticola S1 and Enterobacter sp. Ag1 are gut bacteria in mosquitoes. The intrathoracic injection of the two bacteria can result in an acute hemocoelic infection in the naïve mosquitoes with mortality of ~40% at 24hr post-infection. However, the Enterobacter or Serratia primed mosquitoes showed a better 24hr survival upon the bacterial challenge. The priming confers the protection with a certain degree of specificity, the Enterobacter primed mosquitoes had a better survival upon the Enterobacter but not Serratia challenge, and the Serratia primed mosquitoes had a better survival upon the Serratia but not Enterobacter challenge. To understand the priming-mediated immune enhancement, the transcriptomes were characterized in the mosquitoes of priming as well as priming plus challenges. The RNA-seq was conducted to profile 10 transcriptomes in three priming conditions (native microbiota, Serratia priming, Enterobacter priming), and each priming regime was followed by challenges with the two bacteria, respectively. The three priming regimes resulted in distinctive transcriptomic profiles with about 60% of genes affected by both bacteria. Upon challenges, different primed mosquitoes display different transcriptomic patterns in response to different bacteria. When a primed cohort was challenged with a heterogenous bacterium, more responsive genes were observed than was challenged with a homogenous bacterium. As expected, many canonical immune genes were responsive to the priming and challenge, but much more non-immune genes with various functions were also responsive in the contexts, which implies that the prior priming triggers a delicate and coordinated broad systemic regulation, which results in an enhanced immunity against the subsequent challenge. Besides the participation of typical immune pathways, the transcriptome data suggest the involvement of lysosome and metabolism in the context. Overall, this study demonstrated a trained immunity via priming with bacteria in diet.